Approximation by matrix means on hexagonal domains in the generalized Holder metric - Aslan, Hatice (Univ Nis, Fac Sci Math, 2023)
In this paper the degree of approximation of the function f, which is periodic with respect to the hexagon lattice by matrix means T(A) n (f) of its hexagonal Fourier series in the generalized Holder metric, where A is a lower triangular infinite matrix of nonnegative real numbers with nonincreasing row is estimated.
Keywords: Hexagonal domain; hexagonal Fourier series; generalized Holder class; matrix mean